Skills in Writing Expository Texts of Grade 12 Learners for the Development of Instructional Material - ARSAD, KARIMA; BANGKULIT, NOR-EN (International Journal of Arts, Sciences and Education, 2025)
The study aimed to determine the proficiency of Grade 12 students in expository writing. Findings revealed that students exhibited a low level of proficiency, particularly in content development, idea organization, grammar, and punctuation. In response, a module was developed as a supplementary teaching material to enhance writing skills. The module underwent expert validation and received high evaluations across various aspects, including content, design and organization, text quality, assessment, readability, and references. Additionally, the module was evaluated for acceptance by both teachers and students, who provided positive ratings regarding its clarity, engagement, relevance to the target users, and originality. Results indicated that the module was effective as a teaching tool for writing instruction. Furthermore, an analysis of the differences in teachers’ and students’ acceptance ratings showed no significant disparity, suggesting a consistent recognition of the module’s quality and effectiveness. Overall, the study confirmed that the module is a valuable learning aid that can be implemented on a broader scale. It is recommended that continuous review and improvement be undertaken based on feedback from teachers and students to further develop students’ proficiency in writing expository texts.